Polimerne membrane za ločevanje krvi; kemijska modifikacija njihove površine - Lahovnik, Vesna (Kovine zlitine tehnologije, 1999)
Laboratory prepared membranes from polysulfone (PSf), cellulose acetate (CA), polyamide 4,6 (PA4,6), polyamide 6,6 (PA6,6) and from poly-acrilonitrile-co-acrilic acid (kANAK) were characterized by measuring the thickness, deionized water fluxes and then by porcine blood separation. The surfaces of PSf membranes were modified with the series of Friedel-Crafts electrophilic substitutions of aromatic rings in polysulfone molecules with use of 1-chlorodecane and propylene oxide. We also modified the membrane surface by sulfuric acid. All modified membranes were characterized by measuring thicknesses, deionized water fluxes, by measuring the striming potentials and then by porcine blood separation. We examined the effects of chemical modifications with comparison of properties of "native" and surface chemically modified membranes on blood separation characteristics of polymeric membranes.
Keywords: polimeri; membrane; kemijska modifikacija; površine; ločevanje; kri